Pengaruh Variasi Ukuran Ketebalan Material Terhadap Karakteristik Termoelektrik Sistem C/CuO - Sari, Putri Manda; Putra, Ananda; Zainul, Rahadian; Sanjaya, Hary (Departemen Kimia FMIPA UNP, 2024)
One of the factors that can affect the quality and characteristics of thermoelectric materials is the size of the material.. This study aims to determine how the effect of material size is varied in width and thickness. The material used is activated carbon obtained from previous research that has met the SNI No. 06-3720-1995 content test. The activated carbon is then composited with Copper (II) Oxide. Based on the tests that have been carried out, the best material obtained is the material with a thickness size variation of 0.5 cm. With a high electrical conductivity value of 0.9507 MΩ-.cm-, low thermal conductivity of 0.1805 J/s and has a high Seebeck coefficient of 0.020 mV/K. Thermoelectricity offers sustainable energy to maintain energy needs, namely by converting wasted heat energy into electrical energy that can overcome the current global warming problem.